(untitled) (Bangladesh Journal of Botany, 2022)
Salinity is a major threat to agriculture and its adverse effect on farming land is expanding day by day. In the present study effects of potassium silicate on germination and biochemical parameters of Coriandrum sativum under salt stress were studied. The maximum seed germination (94%) of coriander seeds was observed with potassium silicate. Total chlorophyll content showed the following order: PS > C > NaCl (2mM) + PS > NaCl (4 mM) +PS > NaCl (6mM) +PS > NaCl. Potassium silicate enhanced biochemical components such as sugar, proline, protein and total antioxidant contents in coriander seedlings. The maximum total antioxidant content (46%) was observed in NaCl (6mM) + PS treatment. Hence, potassium silicate acts as a growth stimulating agent and can be used as fertilizer for coriander plants under salt stress. Bangladesh J. Bot. 51(4): 669-675, 2022 (December)